Freire's Problem Posing Concept of Education: A Model for Nigeria System of Education - Nwobodo, Ratzinger E. E. (Journal of Education Review Provision, 2025)
Education is across the globe, rightly considered a veritable tool for a holistic transformative development of both individuals and nations of the world. It is in this line that Fafunwa, an erudite scholar, described education as "the act of informing, forming and strengthening of the powers of the body and mind; a process for transmitting culture for the purpose of continuity and growth and for disseminating knowledge to ensure social control and guarantee rational direction of society" (cited in Ezeani, 2005, p. 13). A critical look at the Nigerian society with her multitude of graduate and postgraduate degree holders leaves one but to wonder whether or not education is indeed key to unlocking the transformative potentials of both individuals and the nation. The disparity and polarization between education and transformation in Nigeria serves as the precursor to our look at Paulo Freire's problem posing education system as an alternative to banking system of education and a way of unearthing the dividends of quality and holistic education in Nigeria. In this light of the above, I ask: what is meant by the banking system of education? What does Freire mean by the problem posing education system? What role would this in Nigeria and Nigerian education system play? What should be done to incorporate this system in the Nigerian system of education? Using the analytic method, this essay reveals that Freire's problem posing education system ought to be adopted in Nigeria if the impact of education must be felt in the Nigerian society. The work suggests that adequate infrastructure, personnel and funding must be provided in order to achieve this.